Factors associated with health-related quality of life in women using path analyses: mediation effect of the adiposity traits - Mahdieh Khodarahmi; Mahdieh Abbasalizad Farhangi; Sahar Khoshro; Parvin Dehghan (BMC, 2021)
Abstract Background The current work aimed to investigate the mediating role of adiposity traits in the relationship between eating behaviors, sleep quality, socio-demographic factors, and the health-related quality of life in women of reproductive age in northwest of Iran. Methods In the current cross-sectional study, a total of 278 overweight and obese women of reproductive age (20-49 y) were enrolled. Anthropometric assessments were performed. Pittsburgh sleep quality index (PSQI) was used for assessment of sleep quality while Short Form 36 (SF-36) questionnaire was used to measure health-related quality of life (HRQoL). Three-Factor Eating Questionnaire-R18 (TFEQ-R18) was used to measure eating behaviors. Path analysis was used to test the relationships between parameters. Results Age was found to be indirectly and negatively associated with mental component score (MCS) (B = − 0.040; P = 0.049) and physical component score (PCS) (B = − 0.065; P = 0.036) through mediatory effects of obesity. Additionally, education was seen to be indirectly and positively related to MCS (B = 0.529; P = 0.045) and PCS (B = 0.870; P = 0.019), respectively. On the other hand, obesity (B = 0.608; P = 0.018) and PSQI score (B = − 0.240; P = 0.034) had direct associations with MCS. Age (B = − 0.065; P = 0.036) and education (B = 0.870; P = 0.019) were also directly associated with obesity. Conclusions Obesity seemed to mediate the effects of socio-demographic parameters on HRQoL. Poor sleep quality was also related to impairment of HRQoL. Further studies are needed to confirm these results.